Endothelial activation and fibrotic changes are impeded by laminar flow-induced CHK1-SENP2 activity through mechanisms distinct from endothelial-to-mesenchymal cell transition - Nguyen, Minh T. H.; Imanishi, Masaki; Li, Shengyu; Chau, Khanh; Banerjee, Priyanka; Velatooru, Loka reddy; Ko, Kyung Ae; Samanthapudi, Venkata S. K.; Gi, Young J.; Lee, Ling-Ling; Abe, Rei J.; McBeath, Elena; et al. (Frontiers in Cardiovascular Medicine, 2023)
The deSUMOylase sentrin-specific isopeptidase 2 (SENP2) plays a crucial role in atheroprotection. However, the phosphorylation of SENP2 at T368 under disturbed flow (Dflow) conditions hinders its nuclear function and promotes endothelial cell (EC) activation. SUMOylation has been implicated in D-flow-induced endothelial-to-mesenchymal transition (endoMT), but the precise role of SENP2 in counteracting this process remains unclear.We developed a phospho-specific SENP2 S344 antibody and generated knock-in (KI) mice with a phospho-site mutation of SENP2 S344A using CRISPR/Cas9 technology. We then investigated the effects of SENP2 S344 phosphorylation under two distinct flow patterns and during hypercholesteremia (HC)-mediated EC activation.